Topical atropine in retarding myopia progression and axial length growth in children with myopia - Alam, Abdur Rahman Mohammad; Hossain, Md. Sanwar; Islam, Md. Shafiqul (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This study was conducted to observe the effect of atropine in retarding myopia progression and axial length growth in 36 myopic children (atropine group, 24; control, 12). The initial spherical equivalent of the atropine group and control group was -3.0 ± 1.6 dioptre and -3.5 ± 1.6 dioptre respectively. At the 12th month in atropine group, it was -2.9 ± 2.6 dioptre and -4.6 ± 1.9 dioptre in the control group. The power of the atropine group reduced but rose in the control group after 12 months. There was a statistically significant difference in final refractive errors between the two groups (p<0.05). The initial axial length of the atropine group and control group was 24.3± 1.0 mm and 24.6 ± 1.1 mm respectively. In 12th month, the changes in axial length in the two groups was insignificant. However, the mean axial length progression at 12 months of the atropine group was -0.1 ± 0.1 mm and it was lower than the control group which was -0.2 ± 0.2 mm, and this was statistically significant (p<0.05). In conclusion, topical atropine (0.01%) retarded myopia progre-ssion and axial length growth in myopic children.